Experimental study on Bio -methane production exhancement from malaysia - Nurul Najiha Shahira Binti Nabil (2023)
There iis iincreasing iawareness ithat irenewable ienergy i(RE) iand ienergy iefficiency iare ivital ifor iboth icreating inew ieconomic iopportunities iand icontrolling ithe ienvironmental ipollution iat ithe iglobal ilevel. iOne iof ithe imost icommon iRE ithat ihave iused iby imany icountries iincluding iMalaysia iis ibiogas. iAnaerobic idigestion i(AD) iin ibiogas iproduction iis ias iknown ias ithe iprocess iby iwhich imicroorganism ibreak idown ibiodegradable imaterial iin ithe iabsence iof ioxygen. iAD ican iuse ito itreat ivariety iof iorganic iwastes iand irecover ibio-energy iin ithe iform iof ibiogas. iBiogas iis iprimarily iconsists iof imethane, icarbon idioxide, iand ithe itrace iamounts iof iother igases iwhich iis icombusted iinto ia iclean iand irenewable isource iof ienergy isuch ias ielectricity iand iheat. iA igreat ialternative ifor iimproving iyields iof iAD iof isolid iwastes iis ithe iAnaerobic iCo-digestion i(AcoD) iof imultiple isubstrates. iAcoD iprocess iis ia ireliable ioption ito iresolve ithe idisadvantages iof isingle isubstrate idigestion isystem iand ienhances ithe ibiogas iyields ipotential idue ito ipositives isynergisms iestablished iin ithe idigestion imedium ias iwell ias ithe isupply iof imissing inutrients iby ithe ico-substrates. iIn iaddition, ico-digestion ioffers iseveral ipossible iecological ieconomical iadvantages. iThe ifeedstock iused iin iAcoD iincludes ianimal imanure, imunicipal isolid iwaste, isewage isludge iand ivarious icrops, iwhich iare ieasy ito iget iand ilow iin icost itoo. iHowever, ithe iprocess iof ioptimization iand iimprovement iof ibiogas iproduction istill iseek ifurther iinvestigations. iBy iusing ithe itechnology iadvancement, iapproaches iand icharacterization imethods iof iorganic iwastes ican iaccelerate ithe itransformation ito iindustrializations, iand irealize ithe isignificant iimprovement iof ibiogas iproduction ias ia irenewable isource iand ieconomically ifeasible ienergy. iThe ievaluation iexhibits, idesigning iand ideveloping ia iframework, iincluding idiverse ifactors ito ienhance ithe ibiogas iproduction iis icritical.